Alcohol-Induced Changes in Conflict Monitoring and Error Detection as Predictors of Alcohol Use in Late Adolescence - Korucuoglu, Ozlem (Neuropsychopharmacology, 2015)
Adolescence is a vulnerable period for the development of substance use and related problems. Understanding how exposure to drugs influences the adolescent brain could reveal mechanisms underlying risk for addiction later in life. In the current study, 87 adolescents (16–20-year olds; the local legal drinking age was16, allowing the inclusion of younger subjects than usually possible) underwent EEG measurements during a Go/No-Go task with and without alcohol cues; after placebo and a low dose of alcohol (0.45 g/kg). Conflict monitoring and error detection processes were investigated with the N2 and the error-related negativity (ERN) ERP components. Participants were followed-up after 6 months to assess changes in alcohol use. The NoGo-N2 was larger for alcohol cues and acute alcohol decreased the amplitude of the NoGo-N2 for alcohol cues. ERN amplitude was blunted for alcohol cues. Acute alcohol decreased the amplitude of the ERN, specifically for control cues. Furthermore, the differences in ERN for alcohol cues between the placebo and alcohol conditions predicted alcohol use 6 months later: subjects who showed stronger blunting of the ERN after acute alcohol were more likely to return to more moderate drinking patterns. These results suggest that cues signalling reward opportunities might activate a go-response mode and larger N2 (detection of increased conflict) for these cues might be necessary for inhibition. The ERN results suggest a deficiency in the monitoring system for alcohol cues. Finally, a lack of alcohol-induced deterioration of error monitoring for cues with high salience might be a vulnerability factor for alcohol abuse in adolescents.